KLASIFIKASI PENERIMA BEASISWA KOPERTIS DENGAN MENGGUNAKAN ALGORITMA C.45 - Tabrani, Muhamad (Jurnal Pilar Nusa Mandiri, 2016)
Every year college get scholarship coordinator private universities (kopertis), Scholarship devoted to student in a college namely scholarship an increase in academic performance (scholarship PPA ) and scholarship assistance learn student (scholarship BBM). The process filing scholarship ppa and bbm through two stages selection selection is the first stage selection in college to determine a candidate scholarship recipients that would be proposed to kopertis, the selection that both the stage in kopertis selection. Many a student who submitted the scholarships as well as surpassing kouta given resulted in the process of select recipients taken longer since select must be in accordance with the criteria so that the recipient scholarship right on target . Based on these problems need a the act of determining scholarship recipients proper. The purpose of this research is to make classifications students scholarship recipients with algorithm C4.5. The results of classifications evaluate and validated with confusion matrix and a curve ROC, the results classifications students scholarship recipients namely algorithm C4.5 with the level of accuracy of 86.88 %, So that it can be applied for the problem the determination of scholarship recipients .